A taxonomia da curadoria de conteúdo no jornalismo móvel digital uma análise do aplicativo Flipboard - Correia, Cynthia Mariah Barreto (2019)
This research has as main objective to identify and to classify the types of curatorship of the information present in the mobile journalism of the aggregator of content Flipboard. In the theoretical foundation, information about digital mobile journalism is presented, as well as its concept, phases, evolution and characteristics. In addition, it provides information on the functionality of content aggregators, especially the mobile platform, and then introduces the concept of content curatorship in journalism, as well as the types of curatorship, which in this paper is dedicated to explore the following: curatorship by subject, algorithmic curatorship, social curatorship, professional curatorship and mixed curatorship. The method used in this research is content analysis, intrinsic to this method is the qualitative and quantitative analysis, both used mutually to identify the presence of content curatorship and then are classified. These methods were also used to achieve one of the proposals of this research that is to identify if the contents of the application aggregator of content, Flipboard, is convergent. Achieving these goals has made it possible to realize that the content available in the content aggregator is convergent but requires that the media that aggregate their content in the app invest more in the use of digital resources and tools to offer users experiences that are more dynamic. In relation to the curatorships, it was identified that Flipboard makes use of all the curators explored in this study, some with greater intensity than others do, but in general it was noticed that all the curators enrolled for this research were present in the app with emphasis on the curatorship algorithmic.